China e a Ásia Central: petróleo, segurança e os Estados Unidos - Ferreira, Kelly de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
In the last two decades, the United States have substantially increased their presence in Central Asia. Therefore their presence left China in an uncomfortable position, as China seeks to build a stable and peaceful environment in its near abroad, having under its influence all the countries of Central Asia. One of the ways used by the Chinese government to get closer to the countries of this region is through the oil. Being so, the Chinese oil companies buy rights of exploitation of oil and gas reserves in Central Asia and through this establishes and deepens friendly ties with these countries. This practice became known as oil diplomacy. This new tool of the Chinese government has a double effect: it increases the projection of the Chinese power and dilutes the American influence in the region. In other words, it displeases the United States, and in turn tries to be even more present in Central Asia. The main goal to be worked in this study is how the oil diplomacy increases Chinese influence in Central Asia and dilutes American power in the region. It also aims to explain how the United States uses its presence in Central Asia and on sea lines of communication used to transport oil to contain the Chinese expansion

Nas últimas duas décadas, os Estados Unidos aumentaram substancialmente sua presença na Ásia Central. Por sua vez, a China sempre buscou construir um ambiente estável e pacífico ao redor de seu próprio território, tendo sob sua influência todos os países da Ásia Central; por isso,o incremento da presença norte-americana na região causou desconforto nos políticos chineses. Uma das formas utilizadas pelos últimos para se aproximar dos países dessa região se dá por meio do petróleo. Dessa forma, as companhias de petróleo da China compram direitos de exploração de reservas ou indústrias de petróleo e gás natural de países da Ásia Central e, por meio das empresas chinesas, estabelece e aprofunda os laços de amizade com países como Cazaquistão, Quirguistão, Uzbequistão, Turcomenistão e Tadjiquistão. A prática ficou conhecida como diplomacia do petróleo. Essa nova ferramenta do governo chinês possibilita um duplo efeito: aumentar a projeção chinesa e diluir a influência norte-americana na região, o que desagrada os Estados Unidos, que, por sua vez, buscam ser ainda mais presentes na Ásia Central. O objetivo desta pesquisa é: como a diplomacia do petróleo possibilita um duplo efeito: aumentar a projeção chinesa e diluir a influência norte-americana na região. E como os Estados Unidos usa sua presença na Ásia Central e nas rotas marítimas de transporte de petróleo para conter a expansão chinesa